1973
DOI: 10.1017/s0033291700049588
|View full text |Cite
|
Sign up to set email alerts
|

The aftermath of boxing

Abstract: SYNOPSIS The brains of 15 retired boxers have been studied and the lives of the men concerned have been investigated in retrospect. A characteristic pattern of cerebral change has been identified which appears not only to be a result of the boxing but also to underlie many features of the punchdrunk syndrome.157 35

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
503
0
8

Year Published

1974
1974
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 786 publications
(535 citation statements)
references
References 27 publications
16
503
0
8
Order By: Relevance
“…CTE was first described symptomatically in the late 1920s as 'punch-drunk' dementia in boxers, 69 was later described as 'dementia pugilistica' , 70 and was first described pathologically in 1973. 71 Since the identification of CTE in a former professional American football player in 2005, 72 and additional intensive pathological studies, this condition has gained widespread public attention, and has now been identified in brains of former ice hockey, baseball, rugby and soccer players, 73 wrestlers, 74 and military veterans. 75,76 The prevalence and incidence of CTE in amateur and professional athletes is still unknown, adding to difficulties in discussing its epidemiology and population risks for athletes.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…CTE was first described symptomatically in the late 1920s as 'punch-drunk' dementia in boxers, 69 was later described as 'dementia pugilistica' , 70 and was first described pathologically in 1973. 71 Since the identification of CTE in a former professional American football player in 2005, 72 and additional intensive pathological studies, this condition has gained widespread public attention, and has now been identified in brains of former ice hockey, baseball, rugby and soccer players, 73 wrestlers, 74 and military veterans. 75,76 The prevalence and incidence of CTE in amateur and professional athletes is still unknown, adding to difficulties in discussing its epidemiology and population risks for athletes.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…9,10 This disease is associated primarily with the buildup of neurofibrillary tangles of hyperphosphorylated tau throughout the brain; however, 52% of cases also present with diffuse amyloid-b (Ab) deposits. 11 There has been difficulty reproducing tau pathology in rodents after rmTBI, and to date the only study that has seen a chronic (21 days after TBI) increase in hyperphosphorylated tau after rmTBI has required the use of aged tau transgenic mice to observe an effect.…”
mentioning
confidence: 99%
“…The neuropathology of CTE was first described by Brandenburg, Hallevorden, and later Corsellis who found several characteristic areas of damage: septum pellucidum, adjacent periventricular gray, frontal and temporal lobes, substantia nigra, cerebellar scarring, and diffuse neuronal loss [7,[14][15]. Although originally described in boxers, CTE has since been found in other sports, including football, wrestling, and hockey as well as in individuals suffering repetitive brain trauma that were not athletes [7,14]. It more recently has also been found in military blast victims.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…In severe cases there is a progressive slowing of movement, a propulsive gait, tremor, masked facies, deafness, dysarthria, dysphagia, ptosis and other ocular abnormalities [7]. Clinical deterioration in CTE typically occurs in three stages [7,14] :…”
Section: Review Clinical Presentationmentioning
confidence: 99%